Ethical and legal aspects of computer network use and abuse: some preliminary findings. - FRANKEL, Mark S. (1995)
Summarizes some of the main points raised at two conferences which (1) mapped out the ethical, legal and technological terrain associated with delineating the boundaries of acceptable behaviour in a shared computing environment; and (2) discussed such issues as privacy, confidentiality, integrity, security and ownership as they relate to data and commuications.